2021
DOI: 10.1039/d1ta03705f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reaction mechanisms at a gas–solid interface for typical air pollutant decomposition

Abstract: Various technologies have been developed towards the air pollution control to mitigate adverse impact of pollutants on human health and ecological environment. Photocatalysis is a promising technology because it can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 277 publications
0
27
0
Order By: Relevance
“…The photocatalytic activity of TiO 2 -loaded filters prepared by different aerosol-assisted methods was evaluated using the pseudo-first-order kinetic and Langmuir–Hinshelwood (L-H) models ( Liu et al, 2005 ; Debono et al, 2011 ; Kim et al, 2012 ). Toluene has been selected as a model pollutant for the evaluation as its photocatalytic degradation mechanism has been investigated extensively ( Marcì et al, 2003 ; Sleiman et al, 2009 ; Bianchi et al, 2014 ; Chen et al, 2021 ). The results from the pseudo-first-order kinetic analysis showed that the photocatalytic activity depended on the preparation conditions of the photocatalytic filters, and the highest activity was achieved with the samples prepared by SA and SG methods ( Figures 10A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic activity of TiO 2 -loaded filters prepared by different aerosol-assisted methods was evaluated using the pseudo-first-order kinetic and Langmuir–Hinshelwood (L-H) models ( Liu et al, 2005 ; Debono et al, 2011 ; Kim et al, 2012 ). Toluene has been selected as a model pollutant for the evaluation as its photocatalytic degradation mechanism has been investigated extensively ( Marcì et al, 2003 ; Sleiman et al, 2009 ; Bianchi et al, 2014 ; Chen et al, 2021 ). The results from the pseudo-first-order kinetic analysis showed that the photocatalytic activity depended on the preparation conditions of the photocatalytic filters, and the highest activity was achieved with the samples prepared by SA and SG methods ( Figures 10A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the existing techniques, such as thermal and catalytic combustion, absorption, biofiltration for eliminating VOCs, 5–7 photocatalytic oxidation (PCO) has attracted much attention due to its low cost and no secondary pollution. 8,9 However, the efficiency and stability of PCO technology still needs to be further improved to meet the practical industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Photocatalysis technology has been well recognized as a promising solution and the use of photocatalysis technology is expected to increase. [5][6][7][8] Previous investigations of photocatalysts have mainly focused on traditional titanium dioxide (TiO 2 ), but its practical application has been seriously hindered by its wide band gap and low visible light absorption. Cerium oxide (CeO 2 ) belongs to traditional n-type semiconductors with a relatively flexible conversion ability between trivalent and tetravalent cerium oxidation states.…”
Section: Introductionmentioning
confidence: 99%